Masyarakat Ekonomi ASEAN 2015 Dan Daya Saing Sumber Daya Manusia - Husnayetti Husnayetti (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
Competition in the labor market will increase towards the implementation of the ASEAN free market by the end of 2015. Thus therefore, improving the quality of human resources is a critical success factor of development and progress of a nation. In contrast, the labor of Indonesia also has a significant opportunity to fill the jobs. It is considering that the population of Indonesia, which reached number 4 in the world. The expansion of the labor market will be able to reduce unemployment and improve the welfare of the community, which is one of the goals of the establishment of the ASEAN economic community if Indonesian workers can compete with foreign labor. The low competitiveness is caused by to the low level of workforce education. To improve the competitiveness of the labor could be conducted by improving education that embodies the hard and soft competencies. The existence of soft skills and hard skills must be balanced, because these skills support each other to achieve a person’s success. To create the both skills then the education sector should be able to develop a balanced curriculum to realize soft skills and hard skills of labor.